Repressive coping, stigmatization, psychological distress, and quality of life among behavioral weight management participants. (August 2016) - Truong, Erin A.K.; Olson, KayLoni L.; Emery, Charles F.
Abstract: Repressive coping has been associated with elevated risk of disease and negative health outcomes in past studies. Although a prior study of healthy men found that repression was associated with lower body mass index (BMI), no study has examined repressive coping among obese individuals. This study examined the relationship of repressive coping with BMI and obesity-relevant psychosocial factors among 104 overweight and obese participants in a behavioral weight management program. Participants completed questionnaires assessing repressive coping, stigmatization, psychological distress, and quality of life. BMI was objectively measured. Repressors reported lower stigmatization, anxiety, and depression as well as higher emotional and weight-related quality of life. Repressors and non-repressors had equivalent BMI and reported similar impairment in physical quality of life, but stigmatization moderated the relationship between repressive coping and physical quality of life ( b  = 0.31, p  = 0.039), reflecting better physical quality of life among non-repressors with lower stigmatization. Obese individuals who engage in repressive coping may tend to underreport psychological symptoms, social difficulties, and impairments in quality of life. Higher physical quality of life among non-repressors with lower stigmatization may reflect a combined influence of coping and social processes in physical quality of life among obese individuals. Highlights: Repressive coping, distress, and stigmatization were examined in obese adults. Repressors reported less distress than non-repressors. Non-repressors with lower stigmatization reported higher physical quality of life.